Reflections on the cliometrics revolution : conversations with economic historians - Cain, Louis P.; Williamson, Samuel H.; Lyons, John S.; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2007)
This volume marks fifty years of an innovative approach to writing economic history often called "The Cliometrics Revolution." The book presents memoirs of personal development, intellectual lives and influences, new lines of historical research, long-standing debates, a growing international scholarly community, and the contingencies that guide and re-direct academic careers. In conversation with cliometricians of the next generation, 25 pioneering scholars reflect on changes in the practice of economic history they have observed and have helped to bring about, examining the rise of Western economies and their economic interrelationships, and the impact of modern economic growth on human health, mortality and even happiness. The conversations presented here are engaging, informative and – more often than one might expect – humorous. Together with a framework provided by the editors, they tell a tale of how cliometricians, their allies and their critics, have helped to transform what we know about the economic past.
chapter Introduction: economic history and cliometrics Anglo-American economic history to World War II 5I Before the New Economic History 9II New Economic History in North America 13III Historical economics in Britain 21IV Controversy: or one thing leads to another 26V Cliometrics over 50 years: retrospect and prospect 36VI -- part Part I: BEFORE THE NEW ECONOMIC HISTORY: North America -- chapter Moses Abramovitz, interviewed by Alexander J. Field -- chapter M. C. Urquhart, interviewed by R. Marvin McInnis -- chapter Anna J. Schwartz, interviewed by Eugene N. White -- chapter Walt W. Rostow, interviewed by John V. C. Nye -- chapter Stanley Lebergott, interviewed by Fred Carstensen -- part Part II: BEFORE THE NEW ECONOMIC HISTORY: Great Britain -- chapter H. J. Habakkuk, interviewed by Mark Thomas -- chapter Phyllis Deane, interviewed by Nicholas F. R. Crafts -- chapter W. A. Cole, interviewed by A. J. H. Latham -- chapter R. C. O. Matthews, interviewed by / Nicholas von Tunzelmann and Mark Thomas -- part Part III: NEW ECONOMIC HISTORIANS: The Elders -- chapter William N. Parker, interviewed by Paul Rhode -- chapter Douglass C. North, interviewed by Gary D. Libecap, / John S. Lyons -- part Part IV: LA LOI LAFAYETTE: Cliometrics at Purdue -- chapter Lance E. Davis, interviewed by Samuel H. Williamson and / John S. Lyons -- chapter Jonathan R. T. Hughes, interviewed by Charles Calomiris -- chapter Nathan Rosenberg, interviewed by William A. Sundstrom -- part Part V: THE EXPATRIATES -- chapter R. M. Hartwell, interviewed by Mark Thomas -- chapter Eric Jones, interviewed by Nancy Folbre and Michael Huberman -- chapter Charles H. Feinstein, interviewed by Mark Thomas -- part Part VI: FROM THE WORKSHOP OF SIMON KUZNETS, ECONOMIST -- chapter Richard A. Easterlin, interviewed by Kenneth L. Sokoloﬀ -- chapter Robert E. Gallman, interviewed by William K. Hutchinson -- chapter Robert W. Fog
Keywords: Economics -- History -- Methodology; Economics -- History -- Statistical methods